Promoting conservation or change? The UNESCO label of world heritage (re)shaping urban morphology in the Old Town of Lijiang, China - Ji Li; Tianchen Dai; Shengchen Yin; Yiqing Zhao; Deniz Ikiz Kaya; Linchuan Yang (Frontiers of Architectural Research, 2022)
The UNESCO label of World Heritage can attract a high number of tourists to heritage properties for their Outstanding Universal Values (OUV). Although international studies have demonstrated the World Heritage system can contribute to stimulating cultural tourism and boosting the local economy, how this heritage-led development process promotes urban conservation and morphological changes in cities is yet to be explored adequately. This paper aims to explore the urban morphology of a historic Chinese city after its inscription on the UNESCO World Heritage List, taking the Old Town of Lijiang as case. The methods of spatial plan analysis and discourse analysis are used to analyse the data. The research findings have demonstrated that, theoretically, the Conzenian approach of urban morphology can be an effective framework for World Heritage OUV-monitoring. Methodologically, the analysis of spatial plans and multi-stakeholder interviews can reveal local urban morphology from macro to micro levels. Case-specifically in Lijiang, urban physical characteristics and building structures have been well maintained while traditional social fabric and neighbourhood networks have almost vanished. This research has incorporated the urban morphology approach into (world) heritage management in China, as well as worldwide, in order to maintain the balance between urban conservation and economic growth.